2017
DOI: 10.3346/jkms.2017.32.8.1304
|View full text |Cite
|
Sign up to set email alerts
|

The Different Clinical Aspects of Pediatric Primary Airway Tumors in the Larynx, Trachea, and Bronchi

Abstract: Primary airway tumors are rare in children and no literature reviewed their characteristics each location. We evaluate the clinical characteristics and outcomes of Korean children with primary airway tumors, from the larynx to bronchi. A retrospective chart review of children with primary tumors of the larynx, trachea, and bronchi at Asan Medical Center from January 2000 to July 2016 was conducted. Nineteen children were diagnosed with primary airway tumors of the larynx (47.4%), trachea (10.5%), and bronchi (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…In children and adolescents, malignant tumors of the larynx are rare. Institutional reviews and case reports in patients under 15 years of age have shown that laryngeal carcinoma accounts for less than 0.1% of malignant head and neck tumors [6], [7], [8], [9], [10].…”
Section: Discussionmentioning
confidence: 99%
“…In children and adolescents, malignant tumors of the larynx are rare. Institutional reviews and case reports in patients under 15 years of age have shown that laryngeal carcinoma accounts for less than 0.1% of malignant head and neck tumors [6], [7], [8], [9], [10].…”
Section: Discussionmentioning
confidence: 99%
“…It accounts for less than 1% of primary pulmonary malignant tumors and 0.1%–0.2% of children with primary respiratory system malignant tumors, primarily arising in school‐age children. Tracheobronchial mucoepidermoid carcinoma can be divided into low, moderate, and highly malignant types 6 . It is usually a low‐grade lesion in children with limited growth and metastasis in the respiratory tract 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…The average age of laryngeal tumor diagnosis was 2 months. 4 Hemangiomas are the most common type of primary airway tumors and 85% of infants with subglottic hemangiomas will present by 6 months of age because of the rapid proliferation phase beginning between 2 and 6 months of age. Subglottic hemangiomas are associated with other facial lesions, especially hemangiomas in the beard distribution.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective chart review, 19 cases of primary airway tumors were identified in children, and 47% were laryngeal. The average age of laryngeal tumor diagnosis was 2 months 4 . Hemangiomas are the most common type of primary airway tumors and 85% of infants with subglottic hemangiomas will present by 6 months of age because of the rapid proliferation phase beginning between 2 and 6 months of age.…”
Section: Discussionmentioning
confidence: 99%